Bumi Luhur Farmer Group is one of the farmer groups that supports environmentally friendly agriculture and is the only farmer group that develops a semi-organic rice business in Wonosari Village under the name "BERAS MAPAN 05" according to its seed variet: Agribusiness Development Strategy for Semi-Organic Rice "Beras Mapan 05" produced by Bumi Luhur Farmer Group Wonosari Village, Puger District, Jember Regency - Hafiya Fitrah Nuralita; Nanang Dwi Wahyono; Tanti Kustiari (Jurnal Ilmiah Inovasi, 2023)
Bumi Luhur Farmer Group is one of the farmer groups that supports environmentally friendly agriculture and is the only farmer group that develops a semi-organic rice business in Wonosari Village under the name "BERAS MAPAN 05" according to its seed variety, namely MAPAN 05 hybrid rice seeds. In developing the semi-organic rice business, Bumi Luhur farmer groups face several obstacles that hinder the development of semi-organic rice business, so it is necessary to provide recommendations for alternative semi-organic rice business development strategies "BERAS MAPAN 05". In supporting the sustainability of semi-organic rice production "BERAS MAPAN 05" there needs to be guidelines to describe the development and implementation strategy. Therefore, it is considered necessary to conduct research as an effort to formulate and design a semi-organic rice development strategy model which is analyzed using Strengths, Weaknesses, Opportunities and Threats (SWOT) and concluded with Quantitative QSPM analysis. The results of the study obtained alternative strategies and the priority of the strategy is to optimize organic rice production through optimal utilization of production inputs and skills possessed by farmers to meet market prospects and increasing demand with the highest TAS value of 5.56